Pengaruh Asimetri Informasi, Tingkat Leverage dan Ukuran Perusahaan Terhadap Praktik Manajemen Laba - Fanny Oktivia Denovis (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2019)
Earnings Management is a phenomenon that is influenced by various factors. Among them are such as information asymmetry, firms size and leverage. In Indonesia, earnings management existing cases of a few years ago. This study aims to investigate the influence of Information Asymmetry, Leverage, and firms size to earnings management practices in the mining sector manufacturing companies listed on the Indonesian Stock Exchange. This study takes the population of the mining sector manufacturing companies listed on the Indonesian Stock Exchange (BEI) 2010-2014. The sampling technique used was purposive sampling method. The analytical method used in this study using multiple linear regression analysis to examine the effect of Information Asymmetry, leverage, and the size of the company as an independent variable, earnings management practices as rhe dependent variable. The results showed that asymmetry of information, leverage, and firms size has effect on earnings management practices in the mining sector manufacturing companies listed in Indonesia Stock Exchange Period 2010-2014